STRATEGI LOBI DAN NEGOSIASI NAHDLATUL ULAMA (NU) DALAM KONFLIK KEBIJAKAN HARI SEKOLAH - Khuswatun Hasanah (IAIN Batusangkar, 2019)
This chapter discusses how the lobbying and negotiation process between the Nahdlatul Ulama (NU) and the government in responding to the five-day school rules stipulated in Permendikbud No. 23 of 2017 concerning School Day until finally Presidential Regulation No. 87 of 2017 concerning Strengthening Character Education (PPK). NU rejects the existence of the five-day school rule because it considers it would destroy the existence of Madrasah Diniyah (Madin) which has long been maintained by NU as a bastion of morality as well as an educational institution that maintains the noble values of Indonesia. Data collection methods used are through primary and secondary data collection in the form of interviews, news analysis, books, and related journals. Various efforts were taken by NU to abolish the five-day school obligation including discussing with Muhammadiyah and lobbying and negotiating with President Joko Widodo. In the process, NU used more Direct Lobbying and Negotiation strategies compared to Muhammadiyah, which in turn led to NU's beneficial results starting from the amendment of the five-day school regulation which was then stipulated in Perpres 87/2017 until NU's success in strengthening Madin's existence through government funding for support the Character Education Program.